2022
DOI: 10.1049/mia2.12224
|View full text |Cite
|
Sign up to set email alerts
|

Embroidered Spoof Surface Plasmon Polariton Transmission Line for Wireless Body Sensor Network

Abstract: A wearable Spoof Surface Plasmon Polariton Transmission Line (SSPP TL) operating at 2.45 GHz designed for embroidery production and on‐body communication is proposed. The SSPP TL supports both even and odd modes launched by near field coupling with a dipole antenna perpendicular and parallel to the TL, respectively. First, the experimental dispersion curves and transmission for the even and odd modes are favourably compared to simulations. Then, experimental transmission for each mode is compared with the Line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…[15][16][17][18][19] A recent study reported a wearable SSPP transmission line with nearly 30 dB enhancement of the transmission efficiency with respect to the transmission of radio waves in free space. [20] Furthermore, an embroidered SSPP transmission line was realized [21] with no transmission degradation even when placed on curved and rectangular surfaces owing to the excellent field-confinement characteristics. Another study proposed a stretchable and self-healing SSPP for wearable wireless communication systems.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] A recent study reported a wearable SSPP transmission line with nearly 30 dB enhancement of the transmission efficiency with respect to the transmission of radio waves in free space. [20] Furthermore, an embroidered SSPP transmission line was realized [21] with no transmission degradation even when placed on curved and rectangular surfaces owing to the excellent field-confinement characteristics. Another study proposed a stretchable and self-healing SSPP for wearable wireless communication systems.…”
Section: Introductionmentioning
confidence: 99%